DAMPAK PENGEMBANGAN OBJEK WISATA PANTAI TAKISUNG TERHADAP PENDAPATAN PEDAGANG DAN MASYARAKAT LOKAL DI KABUPATEN TANAH LAUT - UMI NOR AWALIA (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
The purpose of this research is to know the impact of the development of Takisung beach tourism object to the income of traders and local communities in Tanah Laut District.Method of data collection starts from observation, interviews to the respondents, and Department of Tourism, and documentation. Further research result is analyzed by quantitative descriptive method and data processing techniques with frequency distribution.The result of the research shows that the impact of development of Takisung beach tourism object initially impact on the income of traders and local communities, adding new jobs, but since the last two years the development of Takisung beach tourism object has less impact on income, the income of traders and local communities decreased, and it is caused by the number of new tourism objects, especially beaches in Tanah Laut district, therefore it is causing visitors switch to other tourism objects, thus the income of traders and local communities who participate in the use of the beach also declined.Keywords: Development of Takisung Beach Tourism Object, Income of Traders and Local Communities.